Criminal Justice Reform: From Due Process Model to Reintegrative Model as an Alternative to Criminal Case Resolution - Hajairin Hajairin; Muhammad Mustofa; Tofik Yanuar Chandra (Pelopor Publikasi Akademika, 2023)
The research problem of this study is the reform of criminal justice from the due process model to the reintegrative model as a consequence of the development of criminal law, including in the resolution of criminal cases. The reintegrative model is a process of establishing new norms or values, as a form of adaptation in the enforcement of criminal law with the approaches of restorative justice, penal mediation, and discretion. The research method used is normative legal research, with statutory, historical, comparative, and conceptual approaches. The results of this study indicate that, firstly, the reform of criminal justice from the due process model to the reintegrative model is an effort to integrate several approaches such as restorative justice, penal mediation, and discretion. This approach is introduced as an effort to minimize the dominance of the due process model. Resolving criminal cases using the due process model is not the only model for resolving criminal cases, but there are many alternatives available. The concept of the reintegrative model emerged due to the numerous issues in law enforcement with the current dominance of the due process model in criminal justice, which focuses on imprisonment as punishment. Secondly, the reintegrative model of criminal justice provides an alternative for resolving criminal cases, with several approaches that can be used and maximized, including restorative justice, penal mediation, and discretion. Restorative justice can be applied in resolving various criminal offenses, penal mediation involves resolving criminal cases outside the court through deliberation and consensus, and police discretion is a justified police action in the interest of the public. However, these approaches are not well-implemented because some still perceive that resolving criminal cases using these approaches is not part of the criminal law enforcement process